Los salarios del sector formal e informal en México: análisis de ganancias y pérdidas por formalización - Moreno Treviño, Jorge Omar (UANL. Facultad de Economía, 2007)
Analyzes the differences on wages between formal and informal labor market and estimate the net gains from formalization using the set of treatment effects parameters, namely: Ordinary Least Square (OLS), Average Treatment Effect (ATE), Treatment on the Treated (TT), and Treatment on the Untreated (TUT). In general for Mexico from 2000 to 2003 both men and women with higher levels of education have net gains from switching to the formal sector, while workers with lower levels of education have a negative impact on their expected wages from formalizing. Moreover, large differences prevail by studying the conditional treatment effects, yet they reduce in the period studied. For men, the larger effect are obtained from analyzing the unconditional mean differences and the OLS effect which imply a wage gap of around 33.0 per cent in 2000, but steadily reduces to reach 25.3 in 2003. In contrast, for the same period and gender, the ATE of formality reduces this gap estimation to 14.3 percent and steadily decreases to 11.7 percent. Furthermore, the TUT effect of informal workers seems to be even smaller and also decreasing in time, from 7.5 to 2.6. The estimations and evidence for women are significant, and qualitatively similar. The evidence on this paper suggests that sorting through self-selection accounts for explaining a large fraction of the average difference between formal and informal wages.